KOMITMEN KARYAWAN PADA PERENCANAAN PRODUKSI DALAM RANGKA EFEKTIFITAS PELAKSANAAN PENGELOLAAN LIMBAH - Betsy Sihombing; Sortawati Siregar (Jurnal Green Growth dan Manajemen Lingkungan, 2012)
ABSTRACTHave been done research about commitment of employees in production planning for the effectiveness of waste management implementation at the Department of Polymer PT. TIFICO. This research was conducted at the Factory of PT. TIFICO Tangerang in 2010. Hope this research can be useful to encourage increased employee commitment in production planning to improve the effectiveness of waste management Titan slurry (TiO2), which pertained hazardous materials and toxic waste (B3). This study is descriptive research, and the data in this study are represented in the frequency distribution table and histogram of the commitment of employees in production planning for the effectiveness of waste management implementation. Based on this research, the effectiveness of waste management implementation can be done by the Department of Polymer PT. TIFICO with the approach of the commitment of employees at production planning in the process of polymerization. With a sense take the part of the stimulation of the employee's commitment to creating a new innovation in the production process.So also with the determine the working methods of production planning in the polymerization process can reduce the amount of waste Titan of the process.